Photosynthetic and Respiratory Responses of Two Bog Shrub Species to Whole Ecosystem Warming and Elevated CO2 at the Boreal-Temperate Ecotone - Ward, Eric J.; Warren, Jeffrey M.; McLennan, David A.; Dusenge, Mirindi E.; Way, Danielle A.; Wullschleger, Stan D.; Hanson, Paul J. (Frontiers in Forests and Global Change, 2019)
Peatlands within the boreal-temperate ecotone contain the majority of terrestrial carbon in this region, and there is concern over the fate of such carbon stores in the face of global environmental changes. The Spruce and Peatland Response Under Changing Environments (SPRUCE) facility aims to advance the understanding of how such peatlands may respond to such changes, using a combination of whole ecosystem warming (WEW; +0, 2.25, 4.5, 6.75 and 9 °C) and elevated CO2 (eCO2; +500 ppm) treatments in an intact bog ecosystem. We examined photosynthetic and respiration responses in leaves of two ericaceous shrub species--leatherleaf (Chamaedaphne calyculata (L.) Moench) and bog Labrador tea (Rhododendron groenlandicum (Oeder) Kron & Judd)--to the first year of combined eCO2 and WEW treatments at SPRUCE. We surveyed the leaf N content per area (Narea), net photosynthesis (AST) and respiration (RD25) at 25°C and 400 ppm CO2 and net photosynthesis at mean growing conditions (AGR) of newly emerged, mature and overwintered leaves. We also measured leaf non-structural carbohydrate content (NSC) in mature leaves. The effects of WEW and eCO2 varied by season and species, highlighting the need to accommodate such variability in modeling this system. In mature leaves, we did not observe a response to either treatment of AST or RD25 in R. groenlandicum, but we did observe a 50% decrease in AST of C. calyculata with eCO2. In mature leaves under eCO2, neither species had increased AGR and both had increases in NSC, indicating acclimation of photosynthesis to eCO2 may be related to source-sink imbalances of carbohydrates. Thus, productivity gains of shrubs under eCO2 may be lower than previously predicted for this site by models not accounting for such acclimation. In newly emerged leaves, AST increased with WEW in R. groenlandicum, but not C. calyculata. Overwintered leaves exhibited a decrease in RD25 for R. groenlandicum and in AST for C. calyculata with increasing WEW, as well as an increase of AGR with eCO2 in both species. Responses in newly emerged and overwintered leaves may reflect physiological acclimation or phenological changes in response to treatments.